CTA Annual report 2018 - A year in review: Accelerating Agricultural Transformation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
It is becoming increasingly evident that a strong focus on digitalisation as a means to drive agricultural transformation is bearing dividends in the forms of increased production, better livelihoods, more efficient value chains and ultimately greater food and nutrition security. Digitalisation is also key to attracting youth back to agriculture. The use of a wide range of technologies – from mobile phones to drones – is helping smallholders gain access to the information and data they need to transform their businesses. One of the goals in CTA’s 2016–2020 Strategic Plan was to reach 1 million farmers, and a focus on digitalisation is helping us to achieve that. In many of our activities, there is a strong focus on supporting youth and promoting women empowerment.